2000
DOI: 10.1017/s0012162200000591
|View full text |Cite
|
Sign up to set email alerts
|

Multicore myopathy: respiratory failure and paraspinal muscle contractures are important complications

Abstract: Three ambulant males with multicore myopathy, a rare congenital myopathy, are reported with nocturnal hypoventilation progressing to respiratory failure at the age of 9, 13, and 21 years. Deterioration in these individuals occurred over several months without any precipitating event. Patients had clinical evidence of nocturnal hypoventilation with hypoxaemia and hypercapnia. Forced vital capacity was significantly reduced (20 to 43% of predicted level). These parameters improved on institution of overnight ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A progressive scoliosis, often associated with lateral trunk deviation, and respiratory impairment have typically evolved by the second decade. Respiratory impairment may lead to secondary cardiac failure [7,8,14-16] and is often grossly out of proportion to the overall degree of weakness.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…A progressive scoliosis, often associated with lateral trunk deviation, and respiratory impairment have typically evolved by the second decade. Respiratory impairment may lead to secondary cardiac failure [7,8,14-16] and is often grossly out of proportion to the overall degree of weakness.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Many studies have confirmed that the mechanical imbalance of the spine could lead to scoliosis [2,[7][8][9][10]. Injury of the paraspinal soft tissue beside the spine could result in this mechanical imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are many types of scoliosis caused by known etiological factors. Duchenne muscular dystrophy, thoracotomy, multicore myopathy with paraspinal contractures, contractures and growth disturbances in the hip and pelvis, radiation to the juxtaspinal and fractures to the bony spinal column along with continued exposure to physiological stresses were reported to be the causes of scoliosis [1,4,[7][8][9][10]. The prevalence of these types of scoliosis is much lower than that of AIS, and their physiological characters and treatment principles are different from that of AIS.…”
mentioning
confidence: 99%